A novel platinum(ii) anticancer complex of danysl bis(2-benzothiazolylmethyl)amine with dimethyl sulfoxide as a leaving group: synthesis, cytotoxicity, interaction with DNA and human serum albumin. (15th June 2017) - Chen, Zhanfen; Zhang, Shuping; Zhu, Zhenzhu; Zhang, Yumin
Abstract : A novel mononuclear platinum(ii ) anticancer complex of danysl bis(2-benzothiazolylmethyl)amine with a dimethyl sulfoxide as a leaving group was reported. Abstract : A novel mononuclear platinum(ii ) complex, [PtL (DMSO)Cl]Cl (1, hereL = danysl bis(2-benzothiazolylmethyl)amine), has been synthesized and characterized by ESI-MS, IR spectrum, 1 H NMR, 13 C NMR, molar conductivity, and elemental analysis. The results suggest that in the structure of complex1, a platinum(ii ) ion is coordinated by a tertiary amine nitrogen, a benzothiazole nitrogen, a DMSO sulfur, and an exogenous chlorine ion to form one square mononuclear structure. Complex1 exhibits a cytotoxicity comparable to that of cisplatin against HeLa cell line and more potent activities against A-549 and MCF-7 cell lines. Compared to those ofL, the potent cytotoxicity of1 should result from the coordination of Pt(ii ). DNA binding experiments demonstrate that1 could strongly bind to calf thymus DNA (CT-DNA) by a groove binding mode accompanied with a moderate intercalation and induce a visible conformational variation of DNA. Investigation of the reaction of1 with 5′-GMP by ESI-MS shows that complex1 could first form a 1 : 1 adduct [PtL (DMSO)(GMP) − 2Na + H] + with 5′-GMP and react further with a second equivalent of 5′-GMP to form a 1 : 2 adduct [PtL (DMSO)(GMP)2 − 4Na + 3H] +, which is similar to those of [Pt(en)(DMSO)Cl]Cl and cisplatin. Therefore, the anticancer mechanism of these compounds might well be related to each other. The evalution of the protein binding ability shows that complex1 could bind to human serum albumin (HSA) with a moderate binding affinity, quench the intrinsic fluorescence of HSA, and destroy the tertiary structure of HSA.